Enhancing Conveyor Belt Performance: Evaluating the Impact of In-creased Capacity Using Belt Analyst Software - Gian Villany Golwa; Sari Murdiyati; Muhammad Kevin Satria (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
This study investigates the effects of increasing conveyor belt capacity from 148.5 tons per hour (t/h) to 180 t/h on the overall system performance, employing both manual measurements and simulations using Belt Analyst software. The research aims to evaluate critical parameters such as effective pulling force, motor power requirements, structural load, and belt deflection, which are essential for determining the feasibility and impact of such an upgrade. The analysis reveals that with the capacity increase, the effective pulling force required rises to 14,072 N, while the motor power usage escalates to 15 kW. Concurrently, the structural load experiences a significant increase from 46.144 kg/m to 56.238 kg/m, and belt deflection intensifies from 22 mm to 27 mm. These findings suggest that increasing the conveyor belt capacity to 180 t/h, may lead to increased stress on the structure and belt, which could potentially affect the lifespan and performance of the conveyor system. Furthermore, while the conveyor system's performance enhances at the higher capacity, it also places additional stress on the system's components. The study further examines the implications of these changes, emphasizing the potential risks to the conveyor belt’s structural integrity and the possible reduction in its lifespan due to the increased mechanical stress. It is highlighted that careful consideration and precise engineering adjustments are necessary when planning capacity enhancements to avoid adverse effects on the system's longevity and reliability.